Study on the significant effects of ignition energy and gas volume fraction on gas explosion pressure and flame propagation speed - Liang ZHANG; Fangfang LAI; Jingde XU (Meikuang Anquan)
The maximum flame propagation speed, the peak pressure and the pressure rise rate of gas explosion were studied under the influence of two factors of ignition energy and gas volume fraction, by using the orthogonal experimental method in a closed pipeline with a length of 35 m and a cross-sectional area of 200 mm×200 mm. The significant impact law of gas-air mixture explosion under different ignition energy and gas volume fraction conditions was obtained. The experimental results show that under the same gas volume fraction, the flame propagation speed of gas explosion gradually increases with the extension of propagation distance from the ignition position, reaching the maximum value near the outlet, and the larger the ignition energy is, the greater the flame propagation speed is; under the same ignition energy, the maximum flame propagation speed first increases and then decreases with the increase of gas volume fraction, reaching its maximum at a gas volume fraction of 9.5%; from the analysis of range and significance effects, gas volume fraction and ignition energy and their interaction have significant effects on the maximum flame propagation speed, and the significant effects are as follows: the gas volume fraction > the ignition energy > their interaction; under the same gas volume fraction, the peak pressure and the pressure rise rate of gas explosion both increase with the increase of ignition energy, the larger the ignition energy, the higher the peak pressure and the pressure rise rate; under the same ignition energy, the peak pressure and the pressure rise rate first increase and then decrease with the increase of gas volume fraction, with the maximum value at a gas volume fraction of 9.5%; in the aspects of range and significance effects, the gas volume fraction and the ignition energy have a significant impact on the peak pressure and the pressure rise rate, the significance effects are as follows: the ignition energy > the gas volume fraction, and the interaction between the two has no significant effect on the peak pressure and the pressure rise rate.